2016
DOI: 10.1016/j.bbamem.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminus of the yeast G protein-coupled receptor Ste2p plays critical roles in surface expression, signaling, and negative regulation

Abstract: G protein-coupled receptors (GPCRs) are found in all eukaryotic cells examined to date where they function as membrane-bound proteins that bind a multitude of extracellular ligands to initiate intracellular signal transduction systems controlling cellular physiology. GPCRs have seven heptahelical membrane spanning domains connected by extracellular and intracellular loops with an extracellular N-terminus and an intracellular C-terminus. The N-terminus has been the least studied domain of most GPCRs. The yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…This strategy has been used previously in our lab to determine the involvement of TM regions in dimerization [60]. In a recent report we showed that the N-terminus plays an important role in the regulation of Ste2p signaling [69]. The finding herein begins to reveal at the residue level a possible basis for this regulatory control.…”
Section: Discussionmentioning
confidence: 70%
“…This strategy has been used previously in our lab to determine the involvement of TM regions in dimerization [60]. In a recent report we showed that the N-terminus plays an important role in the regulation of Ste2p signaling [69]. The finding herein begins to reveal at the residue level a possible basis for this regulatory control.…”
Section: Discussionmentioning
confidence: 70%
“…The deletion of residues two through 10 of Ste2p resulted in an overexpression of the receptor on the cell surface, thus implying that this region, or its influence on the conformation of the receptor, acted to negatively regulate receptor expression [ 152 ]. In addition, we had shown previously that residues 20 through 30 formed a β-sheet [ 153 ], and that residues in extracellular loop one (EL1) formed a 3 10 helix [ 154 ].…”
Section: Genetic Manipulation Of the Receptor Structurementioning
confidence: 99%
“…The extracellular domains, intracellular domains, and cytoplasmic C-terminal regions correspond to those predicted for the S. cerevisiae Ste2 and Ste3 (45), as well as P. carinii Map3 receptors (18).…”
Section: Methodsmentioning
confidence: 55%